2020
DOI: 10.3847/2041-8213/ab644b
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt Shrinking of Solar Corona in the Late 1990s

Abstract: We derive the longest uniform record of rotational intensities solar coronal magnetic field since 1968 and compare it with the heliospheric magnetic field (HMF) observed at the Earth. We scale the Mount Wilson Observatory and Wilcox Solar Observatory observations of the photospheric magnetic field to the level of the Synoptic Optical Long-term Investigations of the Sun/Vector Spectro Magnetograph and apply the potential field source surface model to calculate the coronal magnetic field. We find that the evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…Examples include matching total unsigned open flux to that measured in-situ in the solar wind (e.g. Lee et al, 2011;Arden, Norton, and Sun, 2014;Virtanen, Koskela, and Mursula, 2020), matching heliospheric current sheet crossings to those measured in-situ (e.g. Hoeksema, Wilcox, and Scherrer, 1983;Badman et al, 2020), or matching the locations of large open field regions with observations of coronal holes in extreme ultra-violet (EUV) images (e.g.…”
Section: Choice Of Source Surface Heightmentioning
confidence: 99%
“…Examples include matching total unsigned open flux to that measured in-situ in the solar wind (e.g. Lee et al, 2011;Arden, Norton, and Sun, 2014;Virtanen, Koskela, and Mursula, 2020), matching heliospheric current sheet crossings to those measured in-situ (e.g. Hoeksema, Wilcox, and Scherrer, 1983;Badman et al, 2020), or matching the locations of large open field regions with observations of coronal holes in extreme ultra-violet (EUV) images (e.g.…”
Section: Choice Of Source Surface Heightmentioning
confidence: 99%
“…However, there are significant discrepancies between this assumption and physical observations of the corona. Various attempts have been made to address this problem, such as experimenting with a nonspherical source surface (e.g., Levine et al 1982), or allowing the source surface height to vary over time (Virtanen et al 2020). The latter authors showed that the PFSS open magnetic flux derived from two magnetogram data sets can match observations at 1 au, but this cannot be used for prediction since the optimum source surface radius varies in an irregular and unpredictable manner.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there are indications that the photospheric and coronal magnetic structure have suddenly and systematically changed during this time period (e.g. Lukianova and Mursula, 2011;Virtanen, Koskela, and Mursula, 2020).…”
Section: Introductionmentioning
confidence: 99%